Effects of Aging on Neural Stem/Progenitor Cells and Oligodendrocyte Precursor Cells after Focal Cerebral Ischemia in Spontaneously Hypertensive Rats. Issue 4 (April 2016) - Liang, Anna C.; Mandeville, Emiri T.; Maki, Takakuni; Shindo, Akihiro; Som, Angel T.; Egawa, Naohiro; Itoh, Kanako; Chuang, Tsu Tshen; Mcneish, John D.; Holder, Julie C.; Lok, Josephine; Lo, Eng H.; et al.
Aging and vascular comorbidities such as hypertension comprise critical cofactors that influence how the brain responds to stroke. Ischemic stress induces neurogenesis and oligodendrogenesis in younger brains. However, it remains unclear whether these compensatory mechanisms can be maintained even under pathologically hypertensive and aged states. To clarify the age-related remodeling capacity after stroke under hypertensive conditions, we assessed infarct volume, behavioral outcomes, and surrogate markers of neurogenesis and oligodendrogenesis in acute and subacute phases after transient focal cerebral ischemia in 3- and 12-month-old spontaneously hypertensive rats (SHRs). Hematoxylin and eosin staining showed that 3- and 12-month-old SHRs exhibited similar infarction volumes at both 3 and 14 days after focal cerebral ischemia. However, recovery of behavioral deficits (neurological score assessment and adhesive removal test) was significantly less in 12-month-old SHRs compared to 3-month-old SHRs. Concomitantly, numbers of nestin + neural stem/progenitor cells (NSPCs) near the infarct border area or subventricular zone in 12-month-old SHRs were lower than 3-month-old SHRs at day 3. Similarly, numbers of PDGFR-α + oligodendrocyte precursor cells (OPCs) in the corpus callosum were lower in 12-month-old SHRs at day 3. Lower levels of NSPC and OPC numbers were accompanied by lower expression levels of phosphorylated CREB. By day 14 postischemia, NSPC and OPC numbers in 12-month-old SHRs recovered to similar levels as in 3-month-old SHRs, but the numbers of proliferating NSPCs (Ki-67 + nestin + cells) and proliferating OPCs (Ki-67 + PDGFR-α + cells) remained lower in the older brains even at day 14. Taken together, these findings suggest that aging may also decrease poststroke compensatory responses for neurogenesis and oligodendrogenesis even under hypertensive conditions.